PENGARUH PROMOSI, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BATIK TENUN IKAT (Studi Kasus CV Paradila Parengan Maduran) - Sentosa, Bayu; Tsalisah, Muafiyatin Nur (J-MACC : journal of management and accounting, 2021)
This study aims to determine the effect of Promotion, Brand Image and Product Quality on Purchasing Decisions of woven batik. The pupulation in this study is a questionnaire calculation report. This study uses the 2015-2019 observation period. With purposive sampling technique with 75 respondents survived the last 5 years. Data analysis method used in this study is multiple linier regression test. The variables used are Promotion, Brand Image and Product Quality as the independent variable, while the Purchase Decision variable as the dependent variable.the results of this study produce findings that Promotion, Brand Image and Product Quality significantly influence purchasing decisions. Simultaneously, Promotion, Brand Image and Product Quality significantly influence Purchasing Decision of batik woven on CV Paradila Lamongan.